EFEKTIVITAS PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM DAN FACEBOOK @ABOUTTNG PADA UMKM DI KOTA TANGERANG - Indi Prautami, (2021)
An effective way to promote MSMEs is to use social media. This study is a quantitative descriptive study that aims to analyze the Effectiveness of Promotions Through Social Media Instagram and Facebook @Abouttng on MSMEs in Tangerang City with the EPIC model (Empathy, Persuasion, Impact, Communication). The object under study is the promotion of MSMEs in Tangerang City via social media Abouttng. This research was conducted by distributing questionnaires to 100 respondents who had seen the promotion of MSMEs in the city of Tangerang through social media Abouttng. Instrument testing using the SPSS 26.0 program then proceed with the measurement of the EPIC Model. Instagram has the average score of Empathy 4.46, Persuasion 4.34, Impact 4.40, Communication 4.40 all within the very effective scale range. The EPIC Rate of Instagram's is 4.40 which is included in the very effective scale, Instagram @Abouttng is very effective in promoting MSMEs in Tangerang City. Facebook has the average score of Empathy 4.35, Persuasion 4.39, Impact 4.42, Communication 4.43, all within the very effective scale range, the EPIC Rate of Facebook's is 4.39 which is included in the very effective scale range, Facebook @Abouttng is very effective in promoting MSMEs in Tangerang City.